NDRG2 phosphorylation provides negative feedback for SGK1-dependent regulation of a kainate receptor in astrocytes - Matschke, Veronika; Theiss, Carsten; Hollmann, Michael; Schulze-Bahr, Eric; Lang, Florian; Seebohm, Guiscard; Strutz-Seebohm, Nathalie (Frontiers in Cellular Neuroscience, 2015)
Glutamate receptors play an important role in the function of astrocytes. Among their tasks is the regulation of gliotransmission, gene expression and exocytosis of the tissue-type plasminogen activator (tPA), which has an enhancing effect on NMDA receptors and thus prevent over-excitation of neighbouring neurons. The kainate receptor GluK2, which is expressed in neurons and astrocytes, is under tight regulation of the PI3-kinase SGK pathway as shown in neurons. SGK1 targets include N-myc downstream-regulated genes 1 and 2 (NDRG1, NDRG2), proteins with elusive function. In the present study, we analyzed the effects of SGK1, NDRG1, and NDRG2 on GluK2 current amplitude and plasma membrane localization in astrocytes and heterologous expression. We demonstrate that NDRG1 and NDRG2 themselves have no effect on GluK2 current amplitudes in heterologous expressed ion channels. However, when NDRG2 is coexpressed with GluK2 and SGK1, the stimulating effect of SGK1 on GluK2 is suppressed both in heterologous expression and in astrocytes. Here, we reveal a new negative feedback mechanism, whereby GluK2 stimulation by SGK1 is regulated by parallel phosphorylation of NDRG2. This regulation of GluK2 by SGK1 and NDRG2 in astrocytes may play an important role in gliotransmission, modulation of gene expression and regulation of exocytosis of tPA.